Microbial Etiology of Pneumonia: Epidemiology, Diagnosis and Resistance Pattern - Rohana Masood, Afshan Aman, Farooque Karim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In general, pneumonia is defined as the presence of a recent pulmonary infiltrate and signs that the infiltrate was brought on by an infectious agent, such as bacteria, viruses, fungi, or parasites. The fifth most common cause of mortality globally is bacterial pneumonia, causing nearly 2.56 million mortalities each and every year across all age groups, with Sub-Saharan Africa, South Asia, and Southeast Asia having the highest fatality rates. Objective: The most prevalent etiological bacteria, its sensitivity to medications, and the most prevalent associated conditions were examined in this research of pneumonia patients Methods: The medical records of pneumonia patients treated at National Institute of Health, Pakistan from January, 2022 to August, 2022 served as the data source for this cross-sectional study. Result: Among the 121 pneumonia patients, the majority (n=54; 44.62%) were older than 64. Majority (n= 109; 90.09%) of the sample used for the culture examination was sputum. The third-generation empirical antibiotic therapies that were most frequently prescribed were ceftriaxone (n=59; 48.78%) and viccillin SX (n=21; 17.35%). Antibiotics Imipenem (100%), meropenem (96%), and Gentamycin (92%) were all very effective against Klebsiella pneumonia. Conclusion: The most frequent bacteria identified in sputum cultures were Klebsiella pneumoniae and Acinetobacter sp. Antibiotics Imipenem, meropenem, and gentamycin have demonstrated encouraging outcomes, however Klebsiella pneumonia, Acinetobacter sp., and Pseudomonas sp. have demonstrated resistance to Isolate, Tetramycin, Ciprofloxacin and Ceftazidime when compared to other antibiotics. Keywords: pneumonia, Klebsiella pneumoniae, Pseudomonas, epidemiology, diagnosis, resistance pattern